Serum magnesium level and cardiac valve calcification in hemodialysis patients - Shihming Tsai; Yuehong Li; Xianglan Wu (BMC Cardiovascular Disorders, 2023)
Abstract Introduction Cardiac valve calcification is closely related to cardiovascular disease. The aim of this study was to investigate the magnesium level and cardiac valve calcification in hemodialysis patients. Methods A cross-sectional study was conducted in 105 maintenance hemodialysis patients with complete follow-up data from June 2020 to May 2021 in Beijing Tsinghua Changgung Hospital, Tsinghua University. Baseline data, including sex, age, primary disease, liver and kidney function, electrolytes and parathyroid hormone, were recorded. According to their echocardiograms, patients were divided into a cardiac valve calcification group and a noncardiac valve calcification group, and the correlations between valve calcification and clinical data were analyzed. Results Of 105 patients under hemodialysis, 60 (56.6%) were male, with an average age of 62.1 ± 13.5 years and a mean dialysis duration of 58.8 ± 45.4 months. The majority of primary renal diseases were diabetic nephropathy (55, 51.9%). Approximately 64.8% of the 105 maintenance hemodialysis patients had cardiac valve calcification, and 35.2% were in the noncardiac valve calcification group. The independent t test and the chi-square test analysis showed that the cardiac valve calcification group had older age, higher smoking rate, diabetes mellitus, lower extremity arterial occlusion, coronary heart disease, and coronary artery calcification ratio but lower parathyroid hormone, serum calcium, serum magnesium, albumin, prealbumin, and high-density lipoprotein cholesterol levels (P < 0.05). Logistic regression analysis showed that age, diabetes mellitus, coronary artery calcification, lower serum magnesium, lower serum calcium, and lower parathyroid hormone levels were associated with valve calcification. Conclusion The presence of cardiac valve calcification was associated with age, calcium, phosphorus and lower magnesium level. These factors we should pay more attention in clinical practice.